Management Of Glaucoma In Developing Countries: Challenges And Opportunities For Improvement - Delgado MF; Abdelrahman AM; Terahi M; Miro Quesada Woll JJ; Gil-Carrasco F; Cook C; Benharbit M; Boisseau S; Chung E; Hadjiat Y; Gomes JAP (Dove Medical Press, 2019)
Maria Fernanda Delgado,1 Ahmed Mostafa Abdelrahman,2 Malika Terahi,3 Juan Jose Miro Quesada Woll,4 Felix Gil-Carrasco,5 Colin Cook,6 Mohamed Benharbit,7 Sebastien Boisseau,8 Ernestine Chung,8 Yacine Hadjiat,8 José AP Gomes9 1Private Practice and Sociedad de Cirugía Ocular, Bogotá, Colombia; 2Department of Ophthalmology, Cairo University, Cairo, Egypt; 3Ophthalmology Department, CHU Nafissa Hammoud, Algiers, Algeria; 4Department of Ophthalmology, Hospital Central De Policia, Bogota, Colombia; 5Glaucoma Department, Hospital Luis Sánchez Bulnes, Asociación para Evitar la Ceguera en México I.A.P, Mexico City, Mexico; 6Division of Ophthalmology, University of Cape Town, Groote Schuur Hospital, Cape Town, South Africa; 7Centre d’Ophtalmologie et d’Explorations Visuelles, Rabat, Morocco; 8Mundipharma Singapore Holding Pte Limited, Singapore, Singapore; 9Department of Ophthalmology and Visual Science, Federal University of São Paulo, São Paulo, BrazilCorrespondence: Yacine HadjiatMundipharma Singapore Holding Pte Limited, 12 Marina View, #22-01, Asia Square Tower 2, Singapore 018961, SingaporeTel +65 6511 1855Fax +65 6511 1167Email Yacine.Hadjiat@mundipharma.com.sgAbstract: Glaucoma is the leading cause of blindness in the developed and developing world. Not only is the clinical impact of this disease considerable, but associated economic and humanistic burdens – affecting patients, caregivers, and society – are substantial. Since glaucoma is an age-related disorder and populations in many developing countries are aging at a faster pace than in the developed world, increasing attention is being focused on ways to ameliorate the burdens of illness. In this paper, we examine the burdens of glaucoma with particular focus on developing countries, discuss some of the challenges that exist in delivering optimal glaucoma management within budget constraints, and bring into perspective how we could improve current healthcare systems, leverage technology, and strike an appropriate balance between cost and quality of care, thereby offering considerations to payors and policymakers in these countries that may result in longer-term cost savings, while concurrently striving to achieve the WHO Vision on the prevention of blindness and visual impairment.Keywords: cost, quality, preservative-free, ocular surface disease, access, healthcare system, developing